Determinación del costo de producción en la camaronera del señor Calderón Torres José Luis, del cantón Santa Rosa, provincia de El Oro, durante el mes de enero - abril del 2015 - Jaramillo Vera, Mayra Emerita (2016)
This research paper entitled: DETERMINATION OF COST OF PRODUCTION IN THE LORD'S SHRIMP CALDERON JOSE LUIS TORRES, CANTON SANTA ROSA, EL ORO PROVINCE, DURING THE MONTH OF JANUARY TO APRIL 2015, was developed in order to meet one of the pre-opt the engineering degree in Accounting and Auditing CPA requirements., plus feedback with expertise on the determination of cost. Shrimp; according to their economic activities is directly linked to cost accounting for production orders; therefore the elements of this accounting such as materials and supplies, labor and overhead costs of production should be properly accounted for determining the cost of production. The proposed objectives were met in full; It was reached to restructure the plan and operating accounts, inventory of goods, values, rights and obligations that helped determine the assets, liabilities and equity, values recorded in the State Initial Situation; then the transactions were recorded in the journal, purchase orders, receipt of materials, production order, requisition, control cards labor and cost sheet provided to publicize the unit and total costs were developed the production. For the smooth running of the business it is necessary to continue with the determination of the production cost which will allow its owner to make sound decisions when the need arises.